2017
DOI: 10.1111/mmi.13651
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of the outermost spore layer: pieces of the puzzle are coming together

Abstract: Summary Certain endospore-forming soil dwelling bacteria are important human, animal, or insect pathogens. These organisms produce spores containing an outer layer, the exosporium. The exosporium is the site of interactions between the spore and the soil environment and between the spore and the infected host during the initial stages of infection. The composition and assembly process of the exosporium are poorly understood. This is partly due to the extreme stability of the exosporium that has proven to be re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
2
3
0
Order By: Relevance
“…Taken together, these results show that CotY, ExsY and CotE share a common pattern of localization during sporulation, behaving as cap proteins at the MCP forespore pole during engulfment, then after engulfment completion forming a second cap at the MCD spore pole and finally completely encasing the forespore. Thus, CotY and ExsY do not seem to be restricted to the cap or the non-cap regions of the B. cereus exosporium, as previously proposed (5,12,33). We also found that CotY, ExsY and CotE already encased the forespore in most of the sporangia scored at hour 24 ( Fig.…”
Section: Coty Exsy and Cote Follow The Same Assembly Dynamic During supporting
confidence: 86%
See 1 more Smart Citation
“…Taken together, these results show that CotY, ExsY and CotE share a common pattern of localization during sporulation, behaving as cap proteins at the MCP forespore pole during engulfment, then after engulfment completion forming a second cap at the MCD spore pole and finally completely encasing the forespore. Thus, CotY and ExsY do not seem to be restricted to the cap or the non-cap regions of the B. cereus exosporium, as previously proposed (5,12,33). We also found that CotY, ExsY and CotE already encased the forespore in most of the sporangia scored at hour 24 ( Fig.…”
Section: Coty Exsy and Cote Follow The Same Assembly Dynamic During supporting
confidence: 86%
“…5Aiii-iv). Thus, the localization of CotY and ExsY is not confined to the cap or to the non-cap regions of the B. cereus exosporium, respectively, as previously thought (5,12,33).…”
Section: Cote Coty and Exsy Form A Complex In Vivo During Sporulatiosupporting
confidence: 61%
“…5Aiii and iv). Thus, the assembly of the B. cereus exosporium does not seem to be unidirectional, as had been deduced from B. anthracis studies (5,12,35).…”
Section: Discussionmentioning
confidence: 68%
“…Using MTG and a SNAP-fusion for the exosporium cap protein CotY, we showed the existence of a second small exosporium cap at the mother cell distal pole (MCD pole) of ∆ exsY spores not previously observed by TEM 27 , 28 . This indicates that exosporium formation shares more similarities with the B. subtilis model of coat formation than expected 1 , 2 , 42 , 43 . Here, we show that SNAP-cell TMR-star (TMR-star), a fluorescent substrate used to label SNAP-tag fusion proteins, and MTG are both able to specifically bind to the coat surface of B. cereus .…”
Section: Introductionmentioning
confidence: 66%